Teaching English on TikTok: Content Analysis Based on Cognitive Theory of Multimedia Learning - Irene Puspita Wijaya; Wawan Eko Yulianto; Daniel Ginting (EDUCAFL : Journal of Education of English as Foreign Language, 2023)
TikTok has been used as a learning tool and effectively improved students’ knowledge and skills, particularly in language learning. However, the educational content on TikTok may not be compatible with the Cognitive Theory of Multimedia Learning (CTML) principles that could reduce cognitive loads in multimedia learning. This research investigated the use of CTML principles, as well as the use of its features on the videos from one of the popular English Teaching channels on TikTok, @englishvit in order to contribute to educational knowledge about teaching practices with social media technologies. The researchers analyzed 40 out of 175 videos from @englishvit using content analysis through decontextualization, recontextualization, categorization and compilation. This study found that @englishvit’s TikTok videos are compatible with at least three principles of CTML, and some TikTok features could increase the compatibility or violate the CTML principles. These results recommended that teachers in digital education should improve the quality of the learning experience for students by applying principles of CTML and utilizing technology.